Tessier Cleft No. 7: A Case of an Unusual Orofacial Cleft - Mishal Muhammed Haris; J Dimpleja; Zarrin Rahnuma; Monideepa Mitra; Somen Roychowdhury; Prosanta Mondal (Journal of Primary Care Dentistry and Oral Health)
Orofacial clefts are one of the most common congenital defects that have a worldwide prevalence of 1 in 700 live births. Paul Tessier a French surgeon in 1976 classified this wide range of abnormalities into a simplified classification known as Tessier’s classification based on anatomical position of the cleft. It is numbered from 0-14 and is further grouped into 4 groups midline clefts, paramedian clefts, orbital clefts, and lateral clefts. Tessier cleft no.7 is an uncommon lateral facial cleft consisting of macrostomia, muscular diastasis of face, abnormalities of the zygoma, retrognathism of the mandible, alveolar clefts, and presence of accessory maxillae. This article aims to provide insights into clinical and radiographic findings as well as early surgical intervention and treatment protocol for this specific group of patients.